Id‘ā’ al-ḥaq wa ḥudūd al-tasāmuḥ fī tarbīyat al-Islāmīyah: Dirāsah awwalīyah fi al-kutub al-muqarrarah li tadrīs māddah al-Islāmīyah bi al-jāmi‘āt al-Indūnīsīya - Truna, Dody S. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
This article focuses on investigating the statement on truth claim and religious tolerance of the Muslim writers of Islamic Education textbooks for students at tertiary level in Indonesia. The purpose is to study how Islamic teachings, according to their points of view, formulate limits of tolerance in the interaction among adherents of different religions. They believe that the formulation is meant to defend Islam from syncretism, hypocrisy, and heresy and to argue against the concept of unlimited tolerance in the view of the advocates of pluralism and multiculturalism. The first side is ‘defenders’, to call them as groups opposing pluralism and multiculturalism, and the second is ‘the advocates’ of pluralism and multiculturalism.DOI: 10.15408/sdi.v20i3.514